2000
DOI: 10.1099/00207713-50-5-1761
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of gram-positive bacteria based on grpE, encoded by the dnaK operon.

Abstract: The dnaK operon in Gram-positive bacteria includes grpE, dnaJ and, in some members, hrcA as well. Both DnaK and DnaJ have been utilized for constructing phylogenetic relationships among various organisms. Multiple copies exist for dnaK and dnaJ genes in some bacterial genera, as opposed to a single gene copy for grpE and for hrcA, according to the currently available data. Here, we present a partial protein-based phylogenetic tree for Grampositive bacteria, derived by using the amino acid sequence identity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…The data presented here suggest a close relationship between these organisms. This result is generally in agreement with the data obtained from 5S rRNA, 16s RNA and grpE reported by Ahmad et al (1) E. faecalis groES and groEL each have a ribosome-binding site. The putative ribosome-binding site sequence (GGAGG) of E. faecalis GroES was identical to that of S. pneumoniae.…”
Section: Discussionsupporting
confidence: 83%
“…The data presented here suggest a close relationship between these organisms. This result is generally in agreement with the data obtained from 5S rRNA, 16s RNA and grpE reported by Ahmad et al (1) E. faecalis groES and groEL each have a ribosome-binding site. The putative ribosome-binding site sequence (GGAGG) of E. faecalis GroES was identical to that of S. pneumoniae.…”
Section: Discussionsupporting
confidence: 83%
“…As mentioned above the topologies of the trees based on the 16S rRNA gene, gyrB, sodA, dnaK, recA and alaS were very similar, which is largely in agreement with previously published data for these and other bacteria (Eisen, 1995;Huang, 1996;Poyart et al, 1998;Diaz-Lazcoz et al, 1998;Ahmad et al, 2000). The extensive intraspecies and intragenus diversity observed in the ddl-based tree is most probably the result of a previously described hitchhiking effect driven by the penicillin-binding protein 2b gene (pbp2b): interspecies recombinational exchanges at the pbp2b locus (selected for by the use of penicillin) can extend into or through the nearby ddl gene (Enright & Spratt, 1999).…”
Section: Comparing Phylogenetic Trees Based On 'Universal' Genessupporting
confidence: 91%
“…The classification of Gram-positive bacteria into two groups based on DNA GjC content (high and low GjC) is, however, supported by all these chronometers, together with studies on the types of RNaseP (Haas et al, 1996) and DNA polymerase C (Huang & Ito, 1999) that they contain and the organization of their dnaK operons (Segal & Ron, 1996). Inferences within these groups are again varied, with phylogenetic studies on the HrcA (Ahmad et al, 1999) and GrpE (Ahmad et al, 2000) proteins suggesting two separate groups of low-GjC Gram-positive bacteria. The relationship of these two (three) Grampositive groups with the Gram-negative bacteria is also unclear, with the high-GjC group being more closely linked on the basis of RNaseP RNA type (Haas et al, 1996) and the presence of shared indels in S12 protein, dihydroorotate dehydrogenase and pyruvate kinase (Gupta, 1998), whilst the low-GjC group is more closely linked on the basis of shared indels in gyrase A (Gupta, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Phylogenetic trees based on various chronometers have indicated close relationships of Gram-positive bacteria to various groups of other bacteria including the cyanobacteria (Ahmad et al, 1999 ;Eisen, 1995), halobacteria (Gribaldo et al, 1999 ;Haas et al, 1996) and mycoplasmas (Weisburg et al, 1989a), whilst specific links have been suggested to Methanosarcina mazei (Gribaldo et al, 1999) and Borrelia burgdorferi (Eisen, 1995). Likewise, such chronometers also give variable phylogenetic positions for the clostridia (Ahmad et al, 1999(Ahmad et al, , 2000Gribaldo et al, 1999 ;Bustard & Gupta, 1997). Previously, we have sequenced the rpoC gene from various leuconostocs and performed a comparative phylogenetic analysis to discern relationships and the tenet of tachytelic evolution within this group of Gram-positive bacteria (Morse et al, 1996a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation